Community Empowerment Management in Realizing Healthy School - Wihardiyani Wihardiyani; Wahyudi Wahyudi; M. Chiar (JETL (Journal of Education, Teaching and Learning), 2019)
Schools and communities have a very close relationship in realizing school or education goals. But the reality in implementing school activities is sometimes more often separating between schools and surrounding communities. This study aims to describe the planning, implementation, and evaluation of community empowerment in realizing healthy schools at Public Elementary School (SDN) No. 6 Siantan, Siantan District, Mempawah Regency. The approach used in this study is a qualitative approach with a type of case study research. The data analysis model used is Model Miles and Huberman. Based on the research that has been done, the following results are obtained: 1) The process of planning community empowerment in referring to healthy schools has gone well; 2) The implementation of community empowerment has gone well which can be seen through cooperation in both activities between institutions (SDN No. 6 Siantan) and the community; and 3) Evaluation of community empowerment activities in realizing healthy schools carried out at the end of each activity by the principal of the sub-district education office UPT and the school committee.